The Interview as Convergent Point *: Between Qualitative Research and Performance Art - Gerner Nielsen, Inga (Peripeti, 2021)
This article explores how a combination of qualitative research and immersive performance has given Inga Gerner Nielsen insight into her audience’s aesthetic perception and imaginary realm in a performance installation. It begins by affirming that to ask an audience open questions about a performance only provides testimony of the after-rationalizations of their experience. The author introduces a phenomenological interview method which draws on sense-memory techniques directing the interviewee to produce thick descriptions, actualizing the lived experience in the interview. In response to Norman K. Denzin’s call for a performative dialogical social science, Nielsen examines why interview material should be conceptualized as performance and explores how working artistically with the interview setup can serve to highlight inherent power dynamics. The article ends with examples showing how the interview was turned into a central immersive element of Inga Gerner Nielsen’s artworks.